The Effect of Trust and Brand Image to Repurchase Intention in Online Shopping - Riki Wijayajaya, H; Tri Astuti, S R (KnE Social Sciences, 2018)
Online shopping customers are asset that must be maintained by a company because online shopping customers can do repurchase intention in online shopping. In fact, some companies do not put emphasis on maintaining these customers. The aim of the study was analyze effect of e-service quality to customer satisfaction, customer satisfaction to trust and brand image, trust and brand image to repurchase intention in online shopping (Case at Berrybenka online customer in Indonesia). The population was customers who had bought the Berrybenka product, and the number of sample was 130 respondents. The method of analysis was quantitative method with Structural Equation Model (SEM). The results shows that e-service quality had a positive influence on customer satisfaction, customer satisfaction had a positive influence on trust and brand image, trust and brand image had a positive influence on repurchase intention. Keywords: e-service quality, customer satisfaction, trust, brand image and repurchase intention.